The Effect of Mindfulness and Gender on the English Achievement - Daniel Parulian Sipahutar; Ismail Petrus; Eryansyah (Jurnal Pendidikan Indonesia, 2023)
During the pandemic of covid-19, many students have faced social anxiety and stress through the transition from online learning to offline learning. The writer wants to conduct this research due to the finding out of the pandemic and lockdown have brought negative effects for students such as mental health, distress, anxiety, and behavior issues. These conditions are affected students' academic achievement. This study aims to analyze the effect of mindfulness and gender on English achievement. The type of this research is experimental. Factorial design is used to analyze two or more independent and dependent variables. The study is conducted in junior high school. There will be two groups in the study; an experimental group and a control. The experimental group will be given 8 meetings of mindfulness training, while the control group will run as the usual class begins. The result of statistical tests on the English achievement test, the dependent sample t-Test shows that there is a significant interaction effect between mindfulness and English achievement. However, there is no significant interaction effect or joint effect between mindfulness and gender in English achievement. Furthermore, the result of the independent sample t-Test shows, there is a significant difference between the experimental and control group in English achievement. Then, it can be concluded that mindfulness can help students improve their English achievement.